Equity And Resolution: Of Theory To Construction In Daily Of Health Professionals - Claudia Maria Mattos Penna; Maria José Menezes Brito; Fernanda Porto (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
It is a qualitative study, based on the comprehensive sociology that aimed to understand the health workers' conceptions on fairness and resolutivity and how those principles are inserted in their daily practices. Interviews were accomplished with 16 health professionals from the Basic Units of Belo Horizonte-MG. The data were analyzed and structured in three categories: 1) Fairness: the attention to the health founded in the differences; 2) Resolutivity: small answers making the difference; and 3) Family's Health Program as reinvention of the health care: reality or utopia? The conceptions of fairness go from the access subject, right to the service, but it should also be recognized the social differences. The data show that the professionals look for solutions for the problems and users' needs, and they believe that the resolutivity should happen starting from an interdisciplinary practice. It is noticed that the strategy of the family health is a process in construction, stuffed with contradictions, because the learning of a differentiated way of attending is happening in the daily routines of the services, without a previous preparation, however they are learning in that daily practice to make the "health of the population" happen.